Age‐specific risk factor profiles of adenocarcinomas of the esophagus: A pooled analysis from the international BEACON consortium. Issue 1 (26th August 2015) - Drahos, Jennifer; Xiao, Qian; Risch, Harvey A.; Freedman, Neal D.; Abnet, Christian C.; Anderson, Lesley A.; Bernstein, Leslie; Brown, Linda; Chow, Wong‐Ho; Gammon, Marilie D.; Kamangar, Farin; Liao, Linda M.; et al.
<x xml:space="preserve">Abstract</x> Esophageal (EA) and esophagogastric junction (EGJA) adenocarcinoma have been steadily increasing in frequency in younger people; however, the etiology of these cancers is poorly understood. We therefore investigated associations of body mass index (BMI), cigarette smoking, alcohol consumption, gastroesophageal reflux and use of nonsteroidal anti‐inflammatory drugs (NSAIDs) in relation to age‐specific risks of EA and EGJA. We pooled individual participant data from eight population‐based, case–control studies within the international Barrett's and Esophageal Adenocarcinoma Consortium (BEACON). The analysis included 1, 363 EA patients, 1, 472 EGJA patients and 5, 728 control participants. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for age‐specific (<50, 50–59, 60–69, ≥70 years) cancer outcomes, as well as interactions by age. BMI, smoking status and pack‐years, recurrent gastroesophageal reflux and frequency of gastroesophageal reflux were positively associated with EA and EGJA in each age group. Early‐onset EA (<50 years) had stronger associations with recurrent gastroesophageal reflux (OR = 8.06, 95% CI: 4.52, 14.37; peffect modification = 0.01) and BMI (ORBMI ≥ 30vs. <25 = 4.19, 95% CI: 2.23, 7.87; peffect modification = 0.04), relative to older age groups. In contrast, inverse associations of NSAID use were strongest in the oldest age group (≥70 years), although this apparent difference was not statistically significant. Age‐specific associations with EGJA showed similar, but slightly weaker patterns and no statistically significant differences by age were observed. Our study provides evidence that associations between obesity and gastroesophageal reflux are stronger among earlier onset EA cancers.